Foreign collaboration in Indian industry : fourth survey report 1985 - RBI (Bombay, 1985)
The First Survey of Foreign Collaboration in Indian Industry (published in 1968) and the second one (published in 1974) provided data relating to the salient features of effective collaboration agreements in Indian industry.* In more recent years there has been a further rise in foreign collaborations (Table 1) and several changes have occurred in their pattern. The periodic studies like the present one try to up-date data on the developments in foreign collaborations which are playing an important role in the Indian industry. This Survey was designed broadly on the same lines as the earlier surveys and covered all Indian public and private limited companies having (i) foreign company capital participation as on March 31, 1981 and (ii) foreign technical collaboration@ agreements in force on April 1, 1977.
Keywords: India Foreign economic relations